Clinical Management of Conventional Gingivectomy in an Adult Patients with Gingival Enlargement - Manta Fany; Maria Fransisca Utha; Depi Praharani; Melok Aris Wahyukundari; Neira Najatus Sakinah; Peni Pujiastuti; Yuliana Mahdiyah Da’at Arina; Desi Sandra Sari (Sriwijaya Journal of Dentistry, 2025)
Introduction: Gingival enlargement is a pathological overgrowth of gingival tissue commonly associated with chronic inflammation, poor oral hygiene, or local irritants. This condition may compromise periodontal health, esthetics, and oral function, particularly in the anterior region. Surgical intervention, such as gingivectomy, is indicated when fibrotic enlargement persists after initial non-surgical periodontal therapy.  Purpose: This case report aims to describe the clinical management and outcomes of inflammatory gingival enlargement treated with conventional gingivectomy following non-surgical initial periodontal therapy. Case presentation: Two adult patients presented with gingival enlargement in the anterior region accompanied by bleeding during toothbrushing. Clinical examinations revealed firm, fibrotic gingiva with probing depths of approximately 4 mm and no radiographic evidence of alveolar bone loss. Following phase I periodontal therapy, including scaling and root planing, residual gingival overgrowth persisted. Both patients subsequently underwent conventional gingivectomy using a scalpel under local anesthesia. External bevel incisions were performed, followed by gingivoplasty to reestablish physiological gingival contours. Postoperative evaluation at one week demonstrated reduced inflammation, satisfactory wound healing, coral-pink gingiva, and restoration of normal gingival morphology. Conclusion: Conventional gingivectomy was effective in managing persistent inflammatory gingival enlargement after initial periodontal therapy, resulting in improved gingival contour, enhanced esthetics, and facilitation of oral hygiene. Long-term success requires adequate plaque control and elimination of predisposing factors to prevent recurrence.